TCD-DCU at LogCLEF 2009: An Analysis of Queries, Actions, and Interface Languages - ZHOU, DONG; GHORAB, MOHAMMED RAMI ELHUSSEIN (My University, 2009)
This paper describes the collaborative participation of Trinity College Dublin and Dublin City University in the Log Analysis for Digital Societies (LADS) task of LogCLEF 2009 track. An analysis of multilingual search logs was carried out with the objectives of investigating how users from different linguistic or cultural backgrounds behave in search, and how the discovery of patterns in user actions could be used for community identification. Our findings suggest that there is scope for further investigation of how search logs can be exploited to personalise and improve cross-language search as well as improve the TEL search system.
PUBLISHED
This is the working notes paper of the experiments done for LogCLEF 2009 (Log File Analysis task at Cross Language Evaluation Forum 2009). This paper is based on joint collaboration between Trinity College Dublin and Dublin City University
Keywords: Cross-Language Information Retrieval, Log File Analysis, Query Reformulation, Action Patterns